Pengaruh Kompres Hangat Kayu Manis Cinnamomun Burmannii terhadap Nyeri Arthritis Gout pada Lansia di Puskesmas Sei Pancur - Rachmawaty M.Noer; Yulianti Wulandari; Alvany Gustira Salman (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Gout arthritis, or often called gout, is a type of arthritis caused by the accumulation of uric acid crystals in the joints and surrounding tissues. Arthritis itself is a term used to describe inflammation of the joints. The process of gout begins with an increase in uric acid levels in the blood, called hyperuricemia. Gout arthritis sufferers in the world affect approximately 10% to 25% of the world's population, the WHO prevalence of gout arthritis in the world is 34.2%. The type of research used in this study is quantitative research using a quasi-experimental research method, namely the pre-posttest control one group design method. This study is a study conducted on 1 group using an intervention without a comparison. This study has been conducted with a total of 20 elderly people who meet the inclusion and exclusion criteria. It is known that the Sig. (2-tailed) value of 0.00 is greater than 0.05. then there is a significant difference between the results before and after the warm cinnamon water compress. So it can be concluded that there is an effect of warm cinnamon compresses (Cinnamomun Burmannii) on gout arthritis in the elderly at the Sei Pancur Community Health Center.